Preparation and performance characteristics of reduced graphene oxide-based electrolytes of vanadium redox flow battery for green energy storage - Hossain, Md Hasnat; Hossain, Md Showkot; Mohd Radzi, Mohd Amran; Rahman, Saidur; Shafie, Suhaidi (2023)
The vanadium redox-flow battery represents a novel energy storage system that is suitable for power grid applications. This particular redox flow battery system exhibits superior efficacy, affordability, and durability in contrast to its predecessors. Vanadium redox flow batteries encounter several challenges, such as inadequate energy efficiency, low thermal conductivity, suboptimal diffusivity, high resistivity, and elevated liquid density. The potential of reduced graphene oxide (RGO) as an electrolyte's catalyst material in vanadium (IV) electrolytes is currently under investigation with the aim of improving thermal conductivity and diffusivity, while simultaneously reducing resistance. The vanadium (IV) electrolyte-based nanofluid was studied with a different weight percentage of RGO (1wt%, 1.5wt%, and 2wt%). The study involves conducting optical and electrochemical characterizations, including FTIR, UV-Vis, SEM, and EDX. Additionally, CV and thermal properties measurements are performed. The light transmission capacity of RGO was enhanced, as evidenced by FTIR, UV-Vis, SEM, and EDX analyses, which also revealed a smooth 2D layer structure and stable electrolyte solutions. The thermal conductivity of an electrolyte based on RGO exhibits a significant increase of 29.8%, 55.6%, and 72.3% compared to a base solution. Additionally, the resistivity of the RGO-based electrolyte is observed to decrease by 32.7%, 49.4%, 67.1%. At a temperature of 35°C, the addition of 2.0% weight RGO results in the most significant enhancement of thermal conductivity, with an increase of 72.3%. The findings of this research are expected to provide valuable insights for future investigations aimed at enhancing the efficacy of green energy storage technology and facilitating the attainment of sustainable development objectives. These objectives include ensuring universal access to affordable, reliable, sustainable, and eco-friendly modern energy.